Investitionsförderung im Finanzföderalismus: Landespolitische Varianz in der Definition 'finanzschwacher Kommunen' - René Geißler (Wirtschaftsdienst, 2018)
Trotz stabiler Konjunktur und entlastender Maßnahmen von Bund und Ländern sind die kommunalen Investitionen weiterhin von großen Disparitäten geprägt. In Reaktion darauf verabschiedete der Bundestag 2015 das Kommunalinvestitionsförderungsgesetz und stockte die gewährten Finanzmittel 2017 noch einmal auf. Mit den Mitteln wurden erstmalig explizit finanzschwache Kommunen adressiert. Dieses Ziel kreierte jedoch neue föderale Koordinationsbedarfe und Konflikte, denn die Länder waren jeweils für die Definition der Finanzschwäche zuständig. Deren Definitionen variieren erheblich. – – Capital spending of local governments has shown large disparities for many years. This holds despite economic growth and various forms of federal financial assistance. In 2015, the federal government set up special transfers substituting local investments targeting a group of financially weak communities. This programme might be described as a landmark of German fiscal federalism, strengthening the path of growing interdependencies. What stood out about this programme was that it would explicitly address fi nancially weak communities for the first time. Despite using federal funds, each state was allowed to make the decision on its own. In the end, 13 states came up with a large variety of definitions of financially weak communities, motivated by both factual and political reasons. This article presents and analyses the range of definitions of in-between states.
Keywords: H54; H77; 330